Kontekstualisasi Hadits Nabi Tentang Publikasi Di Media Sosial - Lailatul Asuro; Endah Tri Wisudaningsih; Robbby Zidni Ilman ZF (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2025)
The development of the digital era has positioned social media as a primary channel for the dissemination of religious information, including hadith. This transformation provides significant opportunities for Islamic da'wah while simultaneously presenting serious challenges related to source accuracy, contextual precision, and the intention behind publication. The rapid and viral nature of social media platforms increases the risk of distortion in the meaning of hadith when not supported by proper scholarly verification. Therefore, the contextualization of hadith is essential to ensure its relevance to modern life without compromising its authenticity and established Islamic scholarly methodology. This study aims to analyze the contextualization of hadith in the practice of publishing on social media and to formulate ethical guidelines for social media engagement based on hadith perspectives. The research employs a qualitative approach through library research, drawing upon classical hadith collections, scholarly works, and relevant academic literature. Data analysis is conducted descriptively and analytically, incorporating Qur’anic evidence, hadith studies, and the process of takhrij to ensure the validity of the narrations examined. The findings indicate that publishing hadith on social media requires a high level of caution through the application of the principle of tabayyun, namely verifying both the chain of transmission (sanad) and textual content (matan) before dissemination. Moreover, presenting hadith in digital visual formats may reduce or alter its meaning if not accompanied by adequate historical and contextual explanation. Therefore, digital da'wah ethics must be upheld through sincere intention, respectful language, and moral responsibility to prevent misinformation, provocation, and the commercialization of religion.